Analysis, modeling and experimental validation of temperature-changing effect on mechanical properties of pneumatic artificial muscle. (17th September 2018) - Wang, Guolei; Hua, Xiaotong; Xu, Jing; Song, Libin; Chen, Ken
ABSTRACT: This paper focuses on quantify how temperature affects the mechanical properties of pneumatic artificial muscle (PAM). The influence of temperature variations on PAM's structure size and internal friction was analyzed firstly, based on the thermal characteristics of rubber diaphragm and fiber mesh, then a novel model considering the influence of temperature variation is proposed, without any fitting parameter or any parameter with uncertain physical meanings. In order to verify the proposed model, temperature-rising experiments using heating device and continuous operation were both carried out separately. Through the comparison of characteristic curves under different temperatures, PAM's characteristics were proven to be affected by temperature variations. The results show that inside temperature changing of PAM is why there are drifting and time-varying phenomenon of their mechanical characteristics in long-term operation, and the proposed model can predict the variations caused by temperature changing well. Meanwhile, the accuracy of the new model is higher than Chou model and lower than Andrikopoulos model; it is understandable because our new model has no fitting parameters, but the advantage of new model is that it takes temperature as independent variables and, therefore, can be used at different temperatures directly without any calibration. GRAPHICAL ABSTRACT: